APPROACHES TO STRENGTHEN MENTAL HEALTH IN COMPETITIVE WORKFORCE TRAINING (Universal International Scientific Journal, 2026)
This article scientifically and theoretically analyzes the issues of ensuring mental health as an important structural factor in the process of training highly qualified personnel in the education system in the context of globalization. The rapid development of information technologies, socio-economic changes and the intensification of the competitive environment in modern society require special attention to the psychological stability of students. In this context, the article highlights the pedagogical and psychological aspects of maintaining and strengthening the mental health of students, the formation of stress resistance, emotional stability and social adaptation skills.
Keywords: globalization, education system, highly qualified personnel, mental health, psychological stability, stress resistance, emotional stability, social adaptation, pedagogical approaches, psychological support